Effect of laser irradiation protocols on temperature, roughness, and morphology of the root surface after root-end resection - Fiscarelli, Victória Maria [UNESP]; Silva, Ana Lídia Pinheiro [UNESP]; de Oliveira, Eliane Cristina Gulin [UNESP]; Zaniboni, Joissi Ferrari [UNESP]; Besegato, João Felipe [UNESP]; Faraoni, Juliana Jendiroba; Kuga, Milton Carlos [UNESP]; Berbert, Fábio Luiz Camargo Vilella [UNESP] (My University, 2022)
This study evaluated the effect of laser irradiation protocols using Thera Lase Surgery (TL), at 2.5 W (2.5) or 2.7 W (2.7), and Gemini (GE), at 1.2 W (1.2) or 1.5 W (1.5) of potency, on the root-end resection surface, in relation to external root temperature, roughness, and surface morphologic changes after the treatments, in the areas near to the root canal (RC) or external root surface (ER). Fifty teeth were endodontically treated and the root-end were resected 3 mm away from the root apex. The specimens were randomized into 5 groups (n = 10), according to the laser irradiation protocol: Control (CO-DW) without irradiation; (TL-2.5) Thera Lase Surgery, 2.5 W; (TL-2.7) Thera Lase Surgery, 2.7 W; (GE-1.2) Gemini, 1.2 W; and (GE-1.5) Gemini, 1.5 W. The external root temperature change was obtained through the difference between the highest value observed during the irradiation and the value at the beginning of the treatment. The surface roughness (µm) was analyzed by confocal laser microscopy and the apical surface morphology was evaluated by scanning electron microscopy, in RC or ER. The temperature change was similar between the irradiation protocols (p > 0.05). CO-DW and GE-1.5 provided the lowest surface roughness (p < 0.05), regardless of the analyzed area. TL-2.7 and GE-1.7 showed more uniform on apical resected morphology and a higher incidence of dentinal tubules occlusion, but only near the root canal (p < 0.05). Root-end resected surface submitted to TL-2.7 and GE1.7 irradiation protocols are more homogeneous and shown higher incidence of closed dentinal tubules near to root canal, despite providing a surface roughness.
Keywords: apical resection; diode laser; high-level laser; laser irradiation